2003
DOI: 10.1379/1466-1268(2003)8<37:ivrfva>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ3 requirement for VEGFR2-mediated activation of SAPK2/p38 and for Hsp90-dependent phosphorylation of focal adhesion kinase in endothelial cells activated by VEGF

Abstract: Endothelial cell migration, a key process in angiogenesis, requires the coordinated integration of motogenic signals elicited by the adhesion of endothelial cells to extracellular matrices and by angiogenic cytokines such as the vascular endothelial growth factor (VEGF). In this study, we found that addition of VEGF to human umbilical vein endothelial cells cultivated on vitronectin triggers a synergistic interaction between the VEGF receptor VEGFR2 and the clustered integrin receptor alphavbeta3. The interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 61 publications
6
90
1
1
Order By: Relevance
“…Interaction between VEGFR2 and a v b 3 integrin is necessary for VEGF to signal stress-activated protein kinase-2/p38 in normal endothelial cells undergoing angiogenesis. 39 Expression of VEGFR2 and a v b 3 was detected in endothelial cells in SKOV-3 EOC xenografts, 40 but to our knowledge, this is the first report of a relationship between VEGFR2 and integrin expression in EOC cells themselves. Our shRNAKDR OVCAR-3 cells showed altered survival in suspension, which was reflected in their ability to form ascites and subcutaneous cystic tumors in vivo.…”
Section: Vegfr2 Rnai Knockdown Increases Eoc Malignancy Sai Adham Et Almentioning
confidence: 81%
“…Interaction between VEGFR2 and a v b 3 integrin is necessary for VEGF to signal stress-activated protein kinase-2/p38 in normal endothelial cells undergoing angiogenesis. 39 Expression of VEGFR2 and a v b 3 was detected in endothelial cells in SKOV-3 EOC xenografts, 40 but to our knowledge, this is the first report of a relationship between VEGFR2 and integrin expression in EOC cells themselves. Our shRNAKDR OVCAR-3 cells showed altered survival in suspension, which was reflected in their ability to form ascites and subcutaneous cystic tumors in vivo.…”
Section: Vegfr2 Rnai Knockdown Increases Eoc Malignancy Sai Adham Et Almentioning
confidence: 81%
“…We have previously shown that Hsp90 interacts with the VEGFR-2 and this VEGF-promoted effect contributes to signaling to FAK and actin remodeling (Rousseau et al, 2000;Masson-Gadais et al, 2003). Using MS/MS analysis, we have now identified Hsp90␤ as a tyrosine-phosphorylated protein associated to the VEGFR-2.…”
Section: Discussionmentioning
confidence: 93%
“…We currently have no explanation for this finding; however, we do note that most previous studies on p38 signaling in ECs have been performed in monolayer cultures, whereas ECs in this study are embedded in 3-D fibrin gels, which may result in previously unidentified cross-talk between pathways that could confound more simple interpretations. Supporting this hypothesis is a report that VEGFR-2 interacts with the integrin ␣ v␤3 to transduce signals to FAK and p38 that regulate cell movement (Masson-Gadais et al, 2003) and a second report suggesting that ␣2␤1 integrins may signal through p38 to modulate focal adhesions (Sweeney et al, 2003). ECs in 3-D gels will likely be triggering many integrins through matrix interactions, and loss of integrinmediated focal adhesions in the absence of active p38 may trigger cell apoptosis (anoikis).…”
Section: Figurementioning
confidence: 93%